GRAVITY-FLOW DEPOSITS IN THE TOARCIAN PERBLA FORMATION (SLOVENIAN BASIN, NW SLOVENIA) - BOSTJAN ROZIC; ANDREJ SMUC (Rivista Italiana di Paleontologia e Stratigrafia, 2011)
The Perbla Formation represents typical Toarcian clay-rich pelagic sediment of the southern Tethyan passive continental margin. It was deposited in the Slovenian Basin, located in present-day western Slovenia. During the Early Jurassic the basin was surrounded by the Dinaric (Friuli) Carbonate Platform to the south and by the Julian Carbonate Platform to the north. Today, the transitional areas between the platforms and basin are not preserved due to intense Cainozoic thrusting and erosion, with the only record of the evolution of these areas stored in gravity-flow deposits of the Perbla Formation. Coarser turbidites were deposited on the margins of the basin, with other types of gravity-flow deposits, observed mainly in the central part of the basin. These intercalations reflect regionally recognized events that characterized the sedimentary evolution of western Slovenia at the end of the Early Jurassic. Slumps that occasionally developed into debris-flows reflect uneven sea-bottom palaeotopography that originated during a pre- to early-Toarcian phase of accelerated subsidence. The early Toarcian transgression caused drowning of the adjacent carbonate platforms, an event reflected in the composition of coarser turbidites which consist almost exclusively of echinoderm fragments and thin-shelled bivalves. These turbidites originated from drowned platform margins and/or slopes and were subsequently redeposited in proximal parts of the basin.